Correction to: Dietary habits of patients with coronary artery disease in a tertiary-care hospital of Bangladesh: a case-controlled study - Taslima Khatun; Dilara Maqbool; Ferdous Ara; Manika Rani Sarker; Kazi Selim Anwar; Asirul Hoque (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.